PLR (Plastic Lithium Rechargeable) Batteries Using Nanoscale Materials: A Convenient Electrical Energy Power for the Future? - G. Campet; N. Treuil; A. Poquet; S. Y. Hwang; C. Labrugere; A. Deshayes; J. C. Frison; J. Portier; J. M. Reau; J. H. Choy (Active and Passive Electronic Components)
This communication describes the synthesis of: (i) non toxic and low cost nanocrystalline electrode materials which can be advantageously prepared at low temperature; (ii) highly conductive electrolyte membranes formed by the nano-encapsulation within a poly (acrylonitrile)-based polymer matrix of a solution of LiPF6 in organic solvants. The performances of rechargeable PLR (Plastic Lithium Rechargeable) batteries using the above mentioned components are presented.